الدعوة إلى الله نظما وشرحا - سحنون, عثمان (University of eloued جامعة الوادي, 2021)
"تناولت هذه الدراسة جمع جل مسائل علم الدعوة في منظومة علمية من بحر الرجز تقع في 274 بيتا، وقد جَمَعَتْ بين حسن الصياغة، والوضوح في الألفاظ مع شرحها شرحا، واضحا، مختصرا غير مخلٍ مع ربط مسائلها بأدلتها الشرعية من مظانها الأصلية (القرآن الكريم، والتفاسير، ومتون الحديث، وبعض الشروح، وبعض المراجع المعاصرة)؛ مع الحرص الشديد على انتقاءِ الأدلةِ الثابتةِ الصريحةِ، الـمُفْصِحَةِ عَنْ ذَاتِهَا معتمدا في ذلك على المنهج الاِستقرائي، التحليلي، وقد توصلت الدراسة إلى جملة من النتائج؛ أهمها: -يمثل النظم أحد الوسائل النافعة في فهم العلم، وضبطه. -أن الدعوة الإسلامية لابد أن تقتدي بدعوة الأنبياء، والرسل؛ فهم أعرف الخلق بِعِلْمِ الدعوة. -أن الدعوة الإسلامية شاملة لجميع جوانب التي يحتاجها الفرد، والمجتمع في أمور دينه، ودنياه.""This study dealt with the collection of most of the issues of the science of da’wah in a scientific system from Bahr Al-Rajz located in 274 beta, and it combined good formulation, clarity in terms with its explanation, clear, concise and unobtrusive while linking its issues with its legal evidence from its original interpretations (the Holy Qur’an, the interpretations The text of the hadith, some explanations, and some contemporary references); With great care in selecting explicit, consistent, self-revealing evidence based on the inductive and analytical approach, the study reached a number of results; The most important ones: -Systems are one of the useful means in understanding and controlling science. -The Islamic call must be imitated by the call of the prophets and messengers; They know creation by the science of da'wah. -The Islamic call includes all aspects that the individual and society need in matters of his religion and his worldly affairs."
دعوة واعلام
Keywords: الدعوةالى الله, نظم الدعوة , شرح الدعوة , أساليب الدعوة; "The call to God,call systems, Explanation of the invitation,Calling methods"